Caracterização molecular e expressão de aminopeptidase (APNs) de Ostrinia nubilalis HÜBER 1796 (Lepidoptera: Crambidae) - Silva, Najara da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Aminopeptidases N (APNs) are a class of ectoenzymes present in the midgut of lepidopteran larvae, which participates in setting the mode of action of Bacillus thuringiensis toxin (Bt). In this work, two aminopeptidases (OnAPN5 and OnAPN6) were cloned from cells of the intestine Ostrinia nubilalis, Lepidoptera pests of temperate maize. The two sequences were identified as APNs for the presence of motifs HEXXH18 (X) and E GAMEM as well as the signal peptide. The same when analyzed correctly grouped with other aminopeptidase sequences in a tree fenogenética, can check in real time the expression in different tissues (gut, adipose tissue and carcass) from APN5 and APN6 and also a third aminopeptidase analyzed in this step APN7 work, where APN7 showed expression of 7.5 times the carcass when compared with the intestine and 4.9 times in adipose tissue when compared with the intestine while APN5 and APN6 relevant only showed expression in tissue of the intestine. These IDs APNs will facilitate studies to characterize binding interactions with Bt toxins, providing a way to understand and prevent the development of resistance to Cry proteins of B. thuringiensis. This information is fundamental to the development of appropriate strategies for managing pest resistance and its effective control

Aminopeptidases N (APNs) são uma classe de ectoenzimas presentes no intestino médio das larvas de lepidópteros, que participa no cenário do modo de ação das toxinas Bacillus thuringiensis (Bt). No presente trabalho, duas aminopeptidases (OnAPN5 e OnAPN6) foram clonadas a partir células do intestino de Ostrinia nubilalis, lepidópteros praga do milho dos climas temperados. As duas sequências foram identificadas como APNs pela da presença dos motivos HEXXH18(X)E e GAMEM, bem como o peptídeo sinal. As mesmas se agruparam corretamente quando analisadas com outras sequências de aminopeptidase em uma arvore fenogenética, Pode-se verificar a expressão em tempo real em diferentes tecidos (intestinal, adiposo e tegumento) da APN5 e APN6 e também de uma terceira aminopeptidase APN7 analisada nesta etapa do trabalho, onde APN7 apresentou expressão de 7,5 vezes mais no tegumento quando comparado com o intestino e de 4,9 vezes mais no tecido adiposo quando comparado com o intestino enquanto que a APN5 e APN6 apresentaram expressão relevante apenas no tecido do intestino. Estas identificações de APNs irão facilitar estudos para caracterizar interações de ligação com as toxinas Bt, proporcionando uma forma de compreender e evitar o desenvolvimento da resistência às proteínas Cry de B. thuringiensis. Estas informações são fundamentais para a elaboração de estratégias adequadas para o manejo da resistência de pragas e seu efetivo controle
Keywords: Lepidoptero; Pragas - Controle; Larva; Larvae